Adsorption of cadmium by live and dead biomass of plant growth-promoting rhizobacteria. Issue 58 (1st October 2018) - Li, Xingjie; Li, Dongbo; Yan, Zhenning; Ao, Yansong
Abstract : Plant growth-promoting rhizobacteria (PGPR) have been extensively investigated in combination remediation with plants in heavy metal contaminated soil. Abstract : Plant growth-promoting rhizobacteria (PGPR) have been extensively investigated in combination remediation with plants in heavy metal contaminated soil. However, being biosorbent, few studies of live and dead cells of PGPR have been undertaken. Meanwhile, the application of live or dead biomass for the removal of heavy metals continues to be debated. Therefore, this study uses living and non-living biosorbents of Cupriavidus necator GX_5, Sphingomonas sp. GX_15, and Curtobacterium sp. GX_31 to compare their Cd(ii ) adsorption capacities by SEM-EDX, FTIR, and adsorption experiments. In the present study, whether the cells were living or dead and whatever the initial Cd(ii ) concentration was, removal efficiency and adsorption capacity can be arranged as GX_31 > GX_15 > GX_5 ( p < 0.05). However, removal efficiency in live and dead biosorbents was quite different and it greatly affected by the initial Cd(ii ) concentrations. The dead cells exhibited a higher adsorption capacity than the live cells of GX_31. Nevertheless, for GX_5 and GX_15, the loading capacity of the non-living biomass was stronger than that of the living biomass at 20 mg L −1 of Cd(ii ), but the capacity was similar at 100 mg L −1 of Cd(ii ). Minor changes of spectra were found after autoclaving and it seemed that more functional groups of the dead biosorbent were involved in Cd(ii ) binding by FTIR analysis, which also illustrated that the hydroxyl, amino, amide, and carboxyl groups played an important role in complexation with Cd(ii ). Based on these findings, we concluded that the dead cells were more potent for Cd(ii ) remediation, especially for GX_31.